The Process of Implementing Competitive Intelligence in a Service Organization - Rocha, Iasmin; Lopes, Luma Louise Sousa (Journal of Sustainable Competitive Intelligence, 2023)
Purpose: The general objective of this research is to present the process of implementing Competitive Intelligence in a small service organization. Methodology/approach: A descriptive qualitative study was carried out using the Action Research strategy. Different collection techniques (semi-structured interviews, observation, word evocation) and data analysis (content analysis, thematic analysis, benchmarking) were used for each stage of the action research framework. Originality/Relevance: The practical relevance of this research lies in the contribution it makes by presenting in detail the process of implementing CI in the organization studied, indicating possible techniques and tools to be used in the context of small organizations for the effective use of CI. Key findings: The main findings show the effective possibility of using the CI process in a small service organization, and also infer the main differences from its direct competitors, as well as challenging the points of need for maintaining competitive capacity in the company studied. Theoretical/methodological contributions: In theoretical terms, the study advances the gap in the literature by bringing the CI process into applied terms. In addition, this study also contributes by discussing CI as a process that enables evolution in organizational management, and also promotes market knowledge, strategy development and anticipation of future trends, especially for small service organizations. In methodological terms, the use of action research as a strategy in the field of study contributes to the verification of theory and practice, the content of which can serve as a basis for future studies.